Nonlinear developmental trajectory of fear learning and memory. (31st October 2013) - King, Elizabeth C.; Pattwell, Siobhan S.; Sun, Alice; Glatt, Charles E.; Lee, Francis S.
Abstract : The transition into and out of adolescence is a unique developmental period during which neuronal circuits are particularly susceptible to modification by experience. Adolescence is associated with an increased incidence of anxiety disorders in humans, and an estimated 75% of adults with fear‐related disorders met diagnostic criteria as children and adolescents. Conserved neural circuitry of rodents and humans has facilitated neurodevelopmental studies of behavioral and molecular processes associated with fear learning and memory that lie at the heart of many anxiety disorders. Here, we review the nonlinear developmental aspects of fear learning and memory during a transition period into and out of adolescence and provide a discussion of the molecular mechanisms that may underlie these alterations in behavior. We provide a model that may help to inform novel treatment strategies for children and adolescents with fear‐related disorders.